The Effect of Salt Composition on the Stress-Free and Cyclic Corrosion Performance of a Nickel-Based Superalloy - MATHEW HENDERY (2021)
The stress-free corrosion and corrosion fatigue of nickel-based superalloy fine-grain (FG) RR1000 with varying salt compositions has been studied to provide a mechanistic understanding of the hot corrosion damage taking place at exposure temperatures of 600℃, approximately 50℃ lower than that of the current literature. Gas turbine rotors typically experience lower tempeatures than the blades to which they are attached. These temperatures are continually increasing, with the drive to improve power plant efficiencies. The operating temperature range and sulphur containing combustion gases and fuels leave the rotor and blade materials open to attack from hot corrosion. The traditional mechanisms of hot corrosion in gas turbines have been reviewed; type I, transitional, and type II hot corrosion. Additionally, a form of hot corrosion typically observed in fireside boilers (fireside hot corrosion) has been discussed due to the satisfaction of many of the morphology requirements in this study. Characterisation of the differences between type II hot corrosion under stress-free conditions at 600℃ and 700℃ for equivalent salt fluxes, highlighted sulphide particle ingress into the bulk material underneath pits at 600℃, which has only recently been observed at 700℃ in relatively recent work. Potassium-based salts were identified as the most damaging at 600℃, compared to the 98%Na2SO4-2%NaCl typically used in hot corrosion studies at 700℃. Additional testing attempted to identify the influence of potassium versus sodium based salts and their relative sulphate/chloride proportions. Corrosion-fatigue testing identified an unusual threshold stress, above which salts with higher chlorine were more damaging. This is thought to be due to the higher stresses promoting oxide cracking, thus allowing ingress of chlorine to reduce fatigue initiation lives. Below this threshold stress the relative quantity of sulphate appeared controlling, with electron back-scattered diffraction (EBSD) and pit measurement techniques showing pitting damage being necessary to penetrate the strain hardened layer (SHL) in order to promote crack growth.